MENINGKATKAN PEMAHAMAN SISWA SMK PADA KOMPETENSI PENGELOLAAN SAMPAH DENGAN MENGGUNAKAN PENDEKATAN INQUIRI - Asniah Asniah (Universitas Lambung Mangkurat, 2011)
It has been conducting research about Implementation of inquiry guide approach in science integreted learning specially garbage management. There are three formulation of the issues raised in this study, namely: how the learning outcomes of students using the inquiry approach, how the activities of the students asked, answered, doing tasks and present their work and how student responses on learning using the concept of inquiry guided approach to waste management competencies. Research goals to improve student’s understanding of eleventh grade of SMKN 1 Tanjung at Waste Management using inquiri guided approach. The number of respondents is 36 students. Results showed that student learning outcomes in the first cycle has not yet reached the classical completeness which 58.3% (category less) increased to 91.70% (Good categories) in the second cycle, the results of student learning is very low with an average of 60.45 (category is less) on the first cycle and increased to 90.45 in the second cycle. management of learning activities performed by teachers also increased, in the first cycle of 3.51 to 3.84 in the second cycle. This learning get very positive response from eleventh grade of Marketing student, for all students (100%) states excited by learning about waste management by using inquiry guided approach.Key word : improve understanding, garbage, inquiry guided approach